Controlling the nanostructure of epoxy resins: Reaction selectivity and stoichiometry. (9th May 2018) - Morsch, Suzanne; Kefallinou, Zoi; Liu, Yanwen; Lyon, Stuart B.; Gibbon, Simon R.
Abstract: The internal topology of epoxy resins is, for the first time, shown not to be the determining factor for small molecule transport. Whilst epoxy resins comprise the matrix component of many high performance composites, coatings and adhesives, the nanostructure and transport properties of these materials are not well understood. Here, peakforce AFM imaging, in-situ FTIR cure analysis and nanochemical AFM-IR imaging are used to establish the effects of reaction selectivity and stoichiometry on the nanostructure of epoxy-phenolic resins based on bisphenol-A and diglycidyl ether of bisphenol-A. In the presence of excess epoxy, resins transition from exhibiting homogeneous internal nanostructures to the familiar nodular morphology characteristic of epoxies. This occurs as a result of lower reaction selectivity in the presence of increasing catalyst concentrations. Surprisingly however, chemically similar stoichiometric resins with a heterogeneous nanostructure display improved resistance to corrosion breakdown (ion transport) and lower water uptake than the homogeneous resins. Graphical abstract: Image 1 Highlights: Lightly cross-linked epoxy phenolic resins have a chemically heterogeneous nanostructure. Reaction selectivity determines nodular nanostructure formation. Heterogeneous nanostructures do not yield increased water uptake or ion transport.